The Believing Game in Mathematics: Stories in a Discipline of Doubt - Shelly Sheats Harkness; Catherin Pullin Lane; Sue Mau; Amber Brass (Journal of the Assembly for Expanded Perspectives on Learning, 2009)
Many people view mathematics as a discipline of certainty and rigidity. Answers are either right or wrong, and, when they are wrong, it is easy to play the doubting game. We invite readers into our mathematics classrooms as we story our attempts to play the believing game. We provide a lens into how we suspended our own logic, assumptions, and interpretations until we first tried to "unpack, " understand, and honor our students' logic, assumptions, and interpreta· tions. Within our individual stories, elements of tension, surprise, and wonder emerged as collective themes.